2015
DOI: 10.1016/j.bjid.2015.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Use of new antiretroviral drugs and classes in Bahia, Brazil: a real life experience on salvage therapy of AIDS patients

Abstract: Antiretroviral therapy has significantly evolved in the last decade, with an increasing number of new drugs and classes. Currently, even heavily experienced patients can be successfully treated with new regimens. In Brazil, the recent incorporation of some new antiretroviral drugs made it possible to suppress HIV plasma viremia in most treated patients, with significant benefits in terms of quality of life and survival. However, little has been published on outcomes of patients under new drugs-based regimens. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
5
0
3
Order By: Relevance
“…These findings are consistent with those of previous studies that demonstrated the effectiveness of DRV/r to range from 55 to 84.7% (VL < 50 copies/ml), although most of these studies examined the results of only 48 weeks of therapy (Table 6). [8][9][10][11][14][15][16][17][18][19][20][21] Recent European observational studies involving 96 and 144 weeks of follow-up demonstrated an effectiveness of 49.1% (last observation carried forward in a modified intent-to-treat analysis, in experienced-patients DRV/r naı¨ve analyses with VF at baseline) and 79.1%, respectively. 15,17 In São Paulo, Brazil, a recent study by our group at another tertiary centre showed that DRV/r plus an OBR use had an effectiveness of 71% after long term follow-up, demonstrating long-term persistent virological suppression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with those of previous studies that demonstrated the effectiveness of DRV/r to range from 55 to 84.7% (VL < 50 copies/ml), although most of these studies examined the results of only 48 weeks of therapy (Table 6). [8][9][10][11][14][15][16][17][18][19][20][21] Recent European observational studies involving 96 and 144 weeks of follow-up demonstrated an effectiveness of 49.1% (last observation carried forward in a modified intent-to-treat analysis, in experienced-patients DRV/r naı¨ve analyses with VF at baseline) and 79.1%, respectively. 15,17 In São Paulo, Brazil, a recent study by our group at another tertiary centre showed that DRV/r plus an OBR use had an effectiveness of 71% after long term follow-up, demonstrating long-term persistent virological suppression.…”
Section: Discussionmentioning
confidence: 99%
“…However, most have been short-term studies on patients treated for up to 48 weeks, and data on long-term outcomes are scarce. [8][9][10][11] Thus, the objectives of the present study are (i) to evaluate the virological and immunological effectiveness of DRV/r plus an optimized background regimen (OBR) in ART-experienced patients over a followup period of 144 weeks and (ii) to identify factors associated with VF during this long-term follow-up period.…”
Section: Introductionmentioning
confidence: 99%
“…Considerar: 1= DRV/r; 2= DRV/r associado a mais uma droga de terceira linha; ≥3= DRV/r associado a mais 2 drogas de terceira linha. 44,55,55,56,57,84,85 Dentre os estudos observacionais brasileiros de de exames que não condizem com boa adesão, entre outras. 56,94 Outro estudo brasileiro realizado por Brígido et al, 95 Estes resultados abrem luz à discussão do uso de menores doses de DRV/r, de modo a diminuir efeitos adversos e, concomitantemente, incrementar a adesão.…”
Section: Análise Estatísticaunclassified
“…44,55,55,56,57,84,85 Dentre os estudos observacionais brasileiros de de exames que não condizem com boa adesão, entre outras. 56,94 Outro estudo brasileiro realizado por Brígido et al, 95 Estes resultados abrem luz à discussão do uso de menores doses de DRV/r, de modo a diminuir efeitos adversos e, concomitantemente, incrementar a adesão. Estudos recentes realizados com pacientes em supressão virológica, mostraram manutenção satisfatória de CV <50 cópias/ml com a mudança do esquema de ARV para terapia de manutenção única com DRV/r uma vez ao dia, inclusive com doses menores de 600/100mg de DRV/r.…”
Section: Análise Estatísticaunclassified
See 1 more Smart Citation